What’s Old Is New Again: Bacteriophage Therapy in the 21st Century - Aslam, Saima (Antimicrob Agents Chemother, 2019)
We highlight features associated with bacteriophage therapy that make it an attractive treatment option for multidrug-resistant infections and also discuss some of the challenges that need to be considered in the design and execution of clinical trials directed at evaluating the efficacy of bacteriophage therapy in humans.